Mesoscale F Region Neutral Winds Associated With Quasi‐steady and Transient Nightside Auroral Forms. Issue 9 (28th September 2018) - Zou, Ying; Nishimura, Yukitoshi; Lyons, Larry; Conde, Mark; Varney, Roger; Angelopoulos, Vassilis; Mende, Stephen
Abstract: High‐latitude neutral winds often circulate in a two‐cell pattern as driven by large‐scale auroral forcing. However, auroral forcing also occurs in various types of mesoscale forms (i.e., tens to hundreds of kilometers in space and a few to tens of minutes in time) and contains more energy input over mesoscale than large scale. A question arises as to whether and how winds respond to the mesoscale forcing. We characterize F region winds associated with various types of auroral forms using scanning Doppler imagers, auroral imagers, and radars. The auroras examined include a quasi‐steady east‐west elongated arc, a quasi‐steady Harang aurora, transient streamers, and a transient substorm westward traveling surge. We find that winds exhibit distinct spatial structures, appearing as channels, vortices, and reversals. Such structures are consistent with the structures of the plasma flows associated with the auroras. Winds exhibit a temporal evolution very similar to the plasma flows and reach maximum perturbations only < 20 min after the flows. The above results suggest that the thermosphere is closely coupled to the ionosphere/magnetosphere through the ion drag force. The < 20‐min time scale can be partially explained by the strong ionization effect associated with the auroras and partially by the fact that the wind perturbations do not approach the flow perturbations but halt at 20% possibly due to momentum forces other than the ion drag. Key Points: Neutral wind field develops distinct mesoscale spatial structures at F region in association with quasi‐steady and transient auroral forms The mesoscale winds evolve similarly to the plasma flows and reach maximum perturbations only < 20 min later than the flows The responsiveness of mesoscale winds is a result of strong ion‐neutral coupling enhanced by the ionization of the auroral forms